(untitled) (Research, Society and Development, 2025)
Aging can occur in different ways, influenced by the individual’s health throughout life, whether by biological or social factors. Aquatic physiotherapy, also known as hydrotherapy, uses the physical properties of water to promote rehabilitation, muscle strengthening, and pain relief. Therefore, the objective of this study was to investigate, through an integrative literature review, the effects of aquatic physiotherapy on the functionality of older adults, identifying physical and psychosocial benefits and the types of protocols employed. This study is an integrative literature review. The search was conducted in the PubMed, SciELO, LILACS, PEDro, and BVS databases. Six studies published between 2021 and 2025, in Portuguese or English, available in full, that investigated aquatic physiotherapy as a primary intervention for older adults, with functional outcomes, were included. The literature review revealed a consistent body of evidence on the positive effects of aquatic physiotherapy on older adults’ functionality. The results showed that aquatic physiotherapy significantly improves muscle strength, balance, mobility, and autonomy, while also reducing pain and the risk of falls. The physical properties of water, such as buoyancy and hydrostatic pressure, provide a safe, low-impact environment, ideal for rehabilitation and maintaining functional capacity. The conclusion is that aquatic physiotherapy is an effective and integrative intervention, contributing to healthy aging and improving quality of life.